PENGARUH KOMITMEN, IKLIM KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA LUBUKLINGGAU - Reniyati, Reniyati; Sardiyo, Sardiyo; Sutanta, Sutanta (LPPM UNIVERSITAS BINA INSAN, 2020)
This research was conducted in Office of Investment and One Stop Integrated Service Lubuklinggau City. The purpose of research to determine the influence of motivation, work discipline and remuneration of service performance in Office of Investment and One Stop Integrated Service Lubuklinggau City both simultaneously and partially. The sample in this research as many as 41 employees in Office of Investment and One Stop Integrated Service Lubuklinggau City. Data analysis technique used in this research is multiple linear regression test, coefficient of determination test, F test and t test. The results obtained are 1). The partial test (t test) performed proves motivation has a significant effect on employee performance where tcount 4,695 > ttable 2,019 and also sig 0,001 < 0,05. 2). Work Discipline significantly influence the performance where tcount 4,806 > ttable 2,019 and also sig is 0,001 < 0,05. 3). Remuneration significantly influence the performance where tcount 5,817 > ttable 2,019 and also sig is 0,000. 4). Motivation, Work Discipline and Remuneration have significant influence simultaneously on Service in Office of Investment and One Stop Integrated Service Lubuklinggau City, where Fcount 8,203 > Ftable 2,86 and also sig of 0,000 < 0.05.